War is not over when it's over women speak out from the ruins of war - Jones, Ann 1937- (Metropolitan Books, 2010)
In 2007, the International Rescue Committee, which brings relief to countries in the wake of war, wanted to understand what really happened to women in war zones. Answers came through the point and click of a digital camera. On behalf of the IRC, Ann Jones spent two years traveling through Africa, East Asia, and the Middle East, giving cameras to women who had no other means of telling the world what war had done to their lives.